Pattern Separation: A Potential Marker of Impaired Hippocampal Adult Neurogenesis in Major Depressive Disorder - Gandy, Kellen; Kim, Sohye; Sharp, Carla; Dindo, Lilian; Maletic-Savatic, Mirjana; Calarge, Chadi (Frontiers in Neuroscience, 2017)
Adult neurogenesis involves the generation of new neurons, particularly in the dentate gyrus of the hippocampus. Decreased hippocampal neurogenesis has been implicated in both animal models of depression and in patients with major depressive disorder (MDD), despite some inconsistency in the literature. Here, we build upon current models to generate a new testable hypothesis, linking impaired neurogenesis to downstream psychological outcomes commonly observed in MDD. We contend that disruption in adult neurogenesis impairs pattern separation, a hippocampus-dependent function requiring the careful discrimination and storage of highly similar, but not identical, sensory inputs. This, in turn, can affect downstream processing and response selection, of relevance to emotional wellbeing. Specifically, disrupted pattern separation leads to misperceived stimuli (e.g., stimulus confusion), triggering the selection and deployment of established responses inappropriate for the actual stimuli. We speculate that this may be akin to activation of automatic thoughts, described in the Cognitive Behavior Theory of MDD. Similarly, this impaired ability to discriminate information at a fundamental sensory processing level (e.g. impaired pattern separation) could underlie impaired psychological flexibility, a core component of Acceptance and Commitment Therapy of MDD. We propose that research is needed to test this model by examining the relationship between cognitive functioning (e.g. pattern separation ability), psychological processes (e.g. perseveration and psychological inflexibility), and neurogenesis, taking advantage of emerging magnetic resonance spectroscopy-based imaging that measures neurogenesis in-vivo.